2013
DOI: 10.1073/pnas.1320301110
|View full text |Cite
|
Sign up to set email alerts
|

Nfatc1 orchestrates aging in hair follicle stem cells

Abstract: Hair production is fueled by stem cells (SCs), which transition between cyclical bouts of rest and activity. Here, we explore why hair growth wanes with age. We show that aged hair follicle SCs (HFSCs) in mice exhibit enhanced resting and abbreviated growth phases and are delayed in response to tissue-regenerating cues. Aged HFSCs are poor at initiating proliferation and show diminished self-renewing capacity upon extensive use. Only modestly restored by parabiosis, these features are rooted in elevated cell-i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

13
184
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 168 publications
(197 citation statements)
references
References 54 publications
13
184
0
Order By: Relevance
“…While canonical Wnt signaling affects the behavior of many adult stem cells, signaling can be high or low depending on the stem cells and their niche. In the quiescent HFSC niche, perceived Wnt signaling is low, corresponding to the high levels of TCF3, TCF4, and TLEs as well as BMP and calcium signaling, which leads to high levels of nuclear NFATc1, typically viewed as a noncanonical Wnt effector (DasGupta and Fuchs 1999;Merrill et al 2001;Horsley et al 2008;Keyes et al 2013;Lien et al 2014). Reductions in BMP signaling and elevation of canonical Wnt signaling are necessary to stabilize b-catenin, repress TCF3/4, and activate LEF1 to send the stem cells along the hair differentiation lineage ( Fig.…”
Section: Wnt/b-catenin Signaling In Balancing Growth and Differentiatmentioning
confidence: 99%
“…While canonical Wnt signaling affects the behavior of many adult stem cells, signaling can be high or low depending on the stem cells and their niche. In the quiescent HFSC niche, perceived Wnt signaling is low, corresponding to the high levels of TCF3, TCF4, and TLEs as well as BMP and calcium signaling, which leads to high levels of nuclear NFATc1, typically viewed as a noncanonical Wnt effector (DasGupta and Fuchs 1999;Merrill et al 2001;Horsley et al 2008;Keyes et al 2013;Lien et al 2014). Reductions in BMP signaling and elevation of canonical Wnt signaling are necessary to stabilize b-catenin, repress TCF3/4, and activate LEF1 to send the stem cells along the hair differentiation lineage ( Fig.…”
Section: Wnt/b-catenin Signaling In Balancing Growth and Differentiatmentioning
confidence: 99%
“…Thus, distinct mechanisms seem to regulate Prlr expression in different keratinocyte populations. While Nfatc1-independent mechanisms control Prlr expression in the IFE, Nfatc1 promotes Prlr expression in HF SCs, which is likely due to a direct mechanism, since Nfatc1 physically associates with the Prlr promoter in bulge cells (Keyes et al 2013). …”
Section: Nfatc1 Promotes Prlr Expression In Bulge Scsmentioning
confidence: 99%
“…Nfatc1 inhibition induces hair growth through precocious bulge cell proliferation (Horsley et al 2008), and it is not clear whether Nfatc1 inhibition accelerates bulge cell migration to induce HF growth, as in the native hair cycle (Zhang et al 2009). Although CN and Nfatc1 have been implicated in epidermal SC function via distinct molecular events (Horsley et al 2008;Wu et al 2010;Keyes et al 2013), the global role of this signaling pathway in regulating skin SC quiescence has not been fully elucidated.…”
mentioning
confidence: 99%
“…found that the muscle and liver from the aged partner of the heterochronic pairs exhibited youthful levels of regeneration (Conboy et al., 2005). A similar “rejuvenating” effect of young blood has been demonstrated in other organs, including the spinal cord (Ruckh et al., 2012), heart (Loffredo et al., 2013), brain (Katsimpardi et al., 2014) (Villeda et al., 2014), β‐cells (Salpeter et al., 2013), and hair follicles (Keyes et al., 2013). Collectively, these observations suggest that exposure to a “young” environment could prevent or reverse age‐dependent decline in the function of critical organ systems.…”
Section: Introductionmentioning
confidence: 99%